Exploring the determinant of pre-pregnancy care services usage among reproductive ages women in Kedah, Malaysia - Rozaimah Abu Talib,; Idayu Badilla Idris,; Rosnah Sutan,; Norizan Ahmad,; Norehan Abu Bakar,; Sharifah Hildah Shahab, (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2016)
Introduction In Malaysia although mortality rate among women of reproductive ages has reduced over the years, the reduction has been stagnant for the past ten years. In order to achieve the 5th Millennium Development Goal, several measures need to be taken including a proper implementation of pre-pregnancy services in this country. This study explores the awareness, intention and usage of pre-pregnancy care (PPC) services and its determinant among women of reproductive ages in Kedah, Malaysia. Methods This is a qualitative study, which consisted of a focus group discussion (FGD) among women in the ages of 18 to 45 years old from all ethnic groups who attended four government clinics in the state of Kedah. The mothers were chosen through purposive sampling from twelve districts that were selected through a multistage random sampling. A semi-structured questionnaire was utilized during the FGD. The results from the FGD were recorded verbatim and thematic analysis was finalized once saturation of information from respondents was achieved. Results These are two themes was identified, namely personal reasons and reasons of service and there are several subthemes under two main themes. Under the Personal reason themes, the subthemes including awareness and intention to used the services, knowledge, perception, social support and history of medical illness. While under pre-pregnancy care services themes, the subthemes including the promotion of the services, the communication relationship with the health staff, the waiting time and also the accessibility of the service. Conclusions As a conclusion, there is still part of society who was unaware of prepregnancy services and its importance in reducing maternal mortality rate as well as producing good pregnancy outcome. Information and knowledge on pre-pregnancy care services should be disseminated among community members through various means including roadshows and pre wedding workshops.